Relationship of Benefits/Sacrifices Ratio with Repurchase Intention Mediated by Consumer Satisfaction - Nurmalasari, Auliya; Wahyudi, Idam; Bikorin; Primartono, Yoshua Ronaldo (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2025)
Abstract. Advances in technology have brought significant changes to the economic world, notably through online platforms that have made consumers more cautious when purchasing cosmetics products. When selecting products, consumers weigh perceived benefits against sacrifices. The benefits/sacrifices ratio is presumed to influence customer satisfaction and subsequently lead to a repurchase intention. This quantitative study tests these relationships using the cosmetics market as the empirical context. It involved 113 respondents who were purchasing cosmetic products for the first time (purposive sampling). The data analysis results indicate that the benefits/sacrifices ratio significantly and positively affects repurchase intention and customer satisfaction. Moreover, customer satisfaction also significantly influences repurchase intention. Furthermore, the results support customer satisfaction as a mediator between the benefits/sacrifices ratio and repurchase intention. Keywords: Benefits/sacrifices ratio, consumer satisfaction, repurchase intention